A Multicenter Study of Neurocognition in Children with Hypertension: Methods, Challenges, and Solutions - Lande, Marc B. (2013)
Hypertensive adults demonstrate decreased performance on neurocognitive testing compared with that of normotensive controls. There is now emerging, preliminary evidence that children with hypertension also manifest neurocognitive differences when compared to normotensive controls, findings postulated to potentially represent early signs of hypertensive target organ damage to the brain. However, reports in children to date have been limited to database and single-center studies. We have established an ongoing, prospective, multicenter study of neurocognition in children with primary hypertension. This article outlines the study methods, with particular attention to the unique challenges in this area of clinical research. We highlight aspects of the study design that are specifically designed as solutions to these challenges.